Signaling and Discrimination in Collaborative Projects - Onuchic, Paula; Ray, Debraj (American Economic Review, 2023)
We study collaborative work in pairs when potential collaborators are motivated by the reputational implications of (joint or solo) projects. In equilibrium, individual collaboration strategies both influence and are influenced by the public assignment of credit for joint work across the two partners. We investigate the fragility of collaboration to small biases in the public’s credit assignment. When collaborators are symmetric, symmetric equilibria are often fragile, and in nonfragile equilibria individuals receive asymmetric collaborative credit based on payoff-irrelevant “identities.” We study payoff distributions across identities within asymmetric equilibria, and compare aggregate welfare across symmetric and asymmetric equilibria. (JEL A11, D82, I23)